Motivasi Peserta Pelatihan Basic Trauma Cardiac Life Support (BTCLS dengan Pembiayaan Mandiri - Mulyadi Fadjar (LPPM STIKES Mataram, 2023)
Introduction: The main challenge in managing health human resources in Indonesia, among others, is the lack of competency-based training. The objectives of the Mataram Health Training Center include improving the quality of training implementation and developing training programs Purpuse: The research aims to identify participants' motivations for participating in BTCLS training with self-financing. Methods: case study, with descriptive research design. The number of respondents in the research was 35 Basic Trauma and Cardiac Live Support (BTCLS) training participants. The approach used is based on Maslow's Hierarchy of Needs Theory. A survey was conducted using the Motivational Beliefs questionnaire which is a measuring tool in applied psychology, owned by the Human Resource Specialist, Faculty of Psychology, University of Indonesia. Result: showed that training participants with motivation to take part in BTCLS training for self-development motivation were 29% (10 people), motivation to get a sense of appreciation was 29% (10 people), motivation to get a certificate was 26% (9 people), motivation to get pocket money was 14% (5 people ) and motivation to fulfillment of Socialization Needs 3% (1 people). Suggestions: In an effort to produce quality services, nurses need to develop themselves through increasing competence, collaboration between health professions, as well as support and guidance from management. as actors in health development and consumers of health services. To improve the quality of training in the form of motivating training participants, the application of Maslow's theory can be an interesting alternative.